KDS2010, a Newly Developed Reversible MAO-B Inhibitor, as an Effective Therapeutic Candidate for Parkinson's Disease - Nam, Min-Ho; Park, Jong-Hyun; Song, Hyo jung; Choi, Ji Won; Kim, Siwon; 장보고; Yoon, Hyung Ho; Heo, Jun Young; Lee, Hyowon; An, Heeyoung; Kim, Hyeon Jeong; Park, Sun Jun; et al. (SPRINGER, 2021)
Monoamine oxidase-B (MAO-B) is a well-established therapeutic target for Parkinson's disease (PD); however, previous clinical studies on currently available irreversible MAO-B inhibitors have yielded disappointing neuroprotective effects. Here, we tested the therapeutic potential of KDS2010, a recently synthesized potent, selective, and reversible MAO-B inhibitor in multiple animal models of PD. We designed and synthesized a series of alpha-aminoamide derivatives and found that derivative KDS2010 exhibited the highest potency, specificity, reversibility, and bioavailability (> 100%). In addition, KDS2010 demonstrated significant neuroprotective and anti-neuroinflammatory efficacy against nigrostriatal pathway destruction in the mouse MPTP model of parkinsonism. Treatment with KDS2010 also alleviated parkinsonian motor dysfunction in 6-hydroxydopamine-induced and A53T mutant alpha-synuclein overexpression rat models of PD. Moreover, KDS2010 showed virtually no toxicity or side effects in non-human primates. KDS2010 could be a next-generation therapeutic candidate for PD.